Political and Legal Aspects of Transboundary Waters Regulation in Central Asia Faced by the Republic of Kazakhstan - KHAMIT, Aidos Kh.; SHAYAKHMETOVA, Zhanna B.; MUKHANOVA, Ademi T. (Journal of Environmental Management and Tourism, 2019)
The article reveals the legal problems of international legal status and the regime of use of transboundary waters of the Republic of Kazakhstan, which mostly do not have a clear international legal status and the regime of their use. This circumstance worsens the ecological situation in the region, exacerbates the interstate contradictions of the Republic of Kazakhstan with neighbouring countries and has a negative impact on the socio-economic development of the country. The article highlights the interstate problem related to the definition of the regime of use of transboundary waters with the People’ Republic of China that can be solved only on a tripartite basis. Article reveals vulnerability of position of Republic of Kazakhstan in negotiations on transboundary rivers with the People’ Republic of China and necessity to resolve this problem with the participation of the Russian side.